Practices and attitudes of adult psychiatrists regarding methamphetamine-associated psychotic disorder: an internet based survey conducted in Turkey - Mehmet Hamdi Örüm; Yaşar Kapıcı; Doğancan Sönmez; Ali Baran Tanrıkulu; Merve Gümüşay; Onur Koçhan; Dilek Örüm; Çiçek Hocaoğlu (BMC Health Services Research)
Abstract Background Many variables may affect approaches of psychiatrists to methamphetamine-associated psychotic disorder (MAP) treatment. This study was aimed to reach adult psychiatrists actively practicing in Turkey through an internet-based survey and to determine their practices and attitudes to MAP treatment. Methods In this internet-based study, participants were divided into three groups based on their answers: Those who do not follow-up any MAP patient were group 1 (n = 78), partially involved in the treatment process of at least one patient diagnosed with MAP were group 2 (n = 128), completely involved in the treatment process of at least one patient diagnosed with MAP were group 3 (n = 202). Results Psychotropic preferences in insomnia (p < 0.001), typical oral antipsychotic choice (p < 0.001), preferred doses of olanzapine/risperidone/aripiprazole/amisulpride for maintenance treatment (p < 0.001), long-acting injectable antipsychotic use practices (p < 0.001), non-antipsychotic psychotropic use characteristics (p < 0.001), extrapyramidal system side effect experiences (p < 0.001), delirium and life-threatening situations encounter rates (p < 0.001) were significantly different between group 2 and group 3. While the duration of maintenance with antipsychotics in the first MAP episode was similar between group 2 and group 3 (p = 0.254), it was different in the second and subsequent MAP episodes (p < 0.05). A binary logistic regression model containing the experiences of long-acting injectable antipsychotic use, extrapyramidal system side effect, and delirium was created (overall p < 0.001, Nagelkerke R2 = 0.435; Hosmer and Lemeshow test p = 0.203). Conclusions This first study in the field, which examines the current issue in detail, reveals that there are many factors that seriously affect psychiatrists' approaches to MAP treatment in Turkey. Trial registration This study was approved by the Ethics Committee of the Fırat University (Date: 14/09/2023; Number: 2023/12–12).